Medication safety a guide for health care facilities - Manasse, Henri R. (Henri Richard); Thompson, Kasey K. (American Society of Health-System Pharmacists, 2005)
Medication safety is the most challenging goal for pharmacy practice and patient safety professionals in all health care facilities.